Incidence of depression in relation to transportation noise exposure and noise annoyance in the SAPALDIA study. (November 2020) - Eze, Ikenna C.; Foraster, Maria; Schaffner, Emmanuel; Vienneau, Danielle; Pieren, Reto; Imboden, Medea; Wunderli, Jean-Marc; Cajochen, Christian; Brink, Mark; Röösli, Martin; Probst-Hensch, Nicole
Highlights: We studied transportation noise exposure and annoyance with incidence of depression. Annoyance associated with depression risk, independent of noise exposure. Annoyance mediated the indirect effects of road traffic and aircraft noise. In non-movers, there were cumulative noise exposure effects, with additive tendency. Physical activity and daytime sleepiness moderated the annoyance effect. Abstract: Prospective evidence on the risk of depression in relation to transportation noise exposure and noise annoyance is limited and mixed. We aimed to investigate the associations of long-term exposure to source-specific transportation noise and noise annoyance with incidence of depression in the SAPALDIA (Swiss cohort study on air pollution and lung and heart diseases in adults) cohort. We investigated 4, 581 SAPALDIA participants without depression in the year 2001/2002. Corresponding one-year mean road, railway and aircraft day-evening-night noise (Lden) was calculated at the most exposed façade of the participants' residential floors, and transportation noise annoyance was assessed on an 11-point scale. Incident cases of depression were identified in 2010/2011, and comprised participants reporting physician diagnosis, intake of antidepressant medication or having a short form-36 mental health score < 50. We used robust Poisson regressions to estimate the mutually adjusted relative risks (RR) and 95% confidence intervals (CI) of depression, independent of traffic-related air pollution and other potential confounders. Incidence of depression was 11 cases per 1, 000 person-years. In single exposure models, we observed positive but in part, statistically non-significant associations (per 10 dB) of road traffic Lden [RR: 1.06 (0.93, 1.22)] and aircraft Lden [RR: 1.19 (0.93, 1.53)], and (per 1-point difference) of noise annoyance [RR: 1.05 (1.02, 1.08)] with depression risk. In multi-exposure model, noise annoyance effect remained unchanged, with weaker effects of road traffic Lden [(RR: 1.02 (0.89, 1.17)] and aircraft Lden [(RR: 1.17 (0.90, 1.50)]. However, there were statistically significant indirect effects of road traffic Lden [(β: 0.02 (0.01, 0.03)] and aircraft Lden [β: 0.01 (0.002, 0.02)] via noise annoyance. There were no associations with railway Lden in the single and multi-exposure models [(RRboth models : 0.88 (0.75, 1.03)]. We made similar findings among 2, 885 non-movers, where the effect modification and cumulative risks were more distinct. Noise annoyance effect in non-movers was stronger among the insufficiently active (RR: 1.09; 95%CI: 1.02, 1.17; p interaction  = 0.07) and those with daytime sleepiness [RR: 1.07 (1.02, 1.12); p interaction  = 0.008]. Cumulative risks of Lden in non-movers showed additive tendencies for the linear cumulative risk [(RRper 10dB of combined sources : 1.31 (0.90, 1.91)] and the categorical cumulative risk [(RRtriple- vs. zero-source ≥45 dB : 2.29 (1.02, 5.14)], and remained stable to noise annoyance. Transportation noise level and noise annoyance may jointly and independently influence the risk of depression. Combined long-term exposures to noise level seems to be most detrimental, largely acting via annoyance. The moderation of noise annoyance effect by daytime sleepiness and physical activity further contribute to clarifying the involved mechanisms. More evidence is needed to confirm these findings for effective public health control of depression and noise exposure burden.